Screening for Security: The Defence Sector as a Gateway to Broader Economic Control - Kovács , Bálint (European Integration Studies, 2024)
This paper explores certain aspects of defence industrial protectionism, and draws parallels with investment screening, as one of the major tools used to maintain economic security. Investment screening has been used quite often in the case of takeovers in the defence sector. Investments in this area, coming from either strategic partners or adversaries, have previously been blocked in several jurisdictions. While this was viewed as normal, the expansion of this treatment to other areas of the economy is a more recent development. Economic security, as a dimension of national security often takes precedence over liberal market principles. Several economic activities are now subject to screening, resulting in further state involvement in the economy, under the guise of the protection of economic security.